Kontribusi Karang Taruna Dalam Penanganan Bencana Banjir Di Kelurahan Manggarai, Jakarta Selatan - Andika, Rikard; Handawati, Rayuna; A’Rachman, Fauzi Ramadhoan (Peneliti.net, 2024)
Karang Taruna is a community social organization as a forum for youth to develop each member on the basis of awareness and social responsibility by and for the community at the village/district level. The aim of this research is to look at the contribution of Karang Taruna in Manggarai Village, Tebet District - South Jakarta among the community in overcoming the flood problem that occurred in Manggarai Village, Tebet District - South Jakarta. Karang Taruna's contribution to flood management will be analyzed using the Triangulation method, namely by obtaining data from various sources. The results of this research are to determine the contribution of Karang Taruna to handling floods that occurred in Manggarai Village, Tebet sub-district - South Jakarta